Pengaruh Kualitas Informasi Dalam Ulasan Online dan Kualitas Situs Web Terhadap Kepercayaan Konsumen Pada Situs Web Perjalanan Wisata (Studi Pada Traveloka) - Rismayanti, Maya; Sarah, Ira Siti (Jurnal Riset Bisnis dan Investasi, 2021)
Travel websites are the choice of tourists to plan trips efficiently. One of the most popular travel and tour websites in Indonesia is Traveloka.com. Many obstacles and problems occur in an online business especially in terms of online consumer trust, Traveloka.com is no exception. This study aims to assess the information quality of reviews on the website, the quality of the website, customers' trust in the website, and finally the effect of information quality and website quality on online trust. This research uses a quantitative approach. The research questionnaire was distributed to 272 Traveloka.com consumers. The results found that the quality of information, website quality, and online trust of Traveloka.com consumers are at a good level. Moreover, there is a simultaneous and partial influence of the information quality in online reviews and the website quality on the customers' online trust of the Traveloka.com website by contributing a value of 29.6%.